SOCIO-ECONOMIC AND DEMOGRAPHIC PROFILE OF OLDER ELDERLY USERS OF A PRIMARY HEALTH UNIT - Letice de Freitas Pereira; Maria Helena Lenardt; Tatiane Michel; Nathalia Hammerschmidt Kolb Carneiro (Cogitare Enfermagem, 2014)
This quantitative, cross-sectional study aimed to describe the socioeconomic and demographic profile of the older elderly users of a Primary Health Unit in the city of Curitiba, State of Parana, Brazil. The study included 100 elderly people of 80 years or over, selected by inclusion and exclusion criteria, in the sample period from February to April 2011. Data were collected through a semi-structured questionnaire and analyzed through descriptive statistics. Results showed a higher number of white women, widows, aged between 80 and 84 years, family income of one minimum wage, without occupation, who live with children or alone. The characteristics highlighted in the socioeconomic and demographic profile of the elderly people may compromise their health and well-being. An intensification of geriatric care programs and activities directed towards the social inclusion of old age is recommend.